Sina-cosa=0.5
(sina-cosa)^2=0.25
1-2sinacosa=0.25
-2sinacosa=-0.75
sinacosa=0.375
( (sin^2a)^3+(cos^2a)^3 )/0.125=( (sin^2a+cos^2a)(sin^4-sin^2a*cos^2a+cos^4a) )/0.125
=1*(sin^4-sin^2a*cos^2a+cos^4a) )/0.125=
(sin^4a-sin^2a*cos^2a+cos^4a-sin^2a*cos^2a+sin^2a*cos^2a) )/0.125=
( (si^2a-cos^2a)^2+sin^2a*cos^2a)/0.125=
( (sina-cosa)^2*(sina+cosa)^2+sin^2acos^2a)/0.125=
(0.25*(sin^2a+2sina*cosa+cos^2a)+sin^2acos^2a)/0.125=
(0.25(1+2sinacosa)+sin^2acos^2a)/0.125=
(0.25(1+2*0.375)+0.375^2)/0.125=
(0.25*1.75+0140625)/0.125=
(0.4375+0140625)/0.125=0.578125/0.125=4.625